Triple-negative accessory breast cancer occurring concurrently with primary invasive breast carcinoma: a case report - Chen, Ling; Wu, Zujian; Guo, Chi; Wan, Hengjin; Wu, Shouguo; Wang, Guoping (Frontiers in Surgery, 2024)
Accessory breast cancer (ABC) is a extremely rare, particularly the presence of triple negative ABC with ipsilateral invasive in situ breast cancer. Binary breast tumors are controversial in terms of surgical methods and comprehensive treatment.We share the case of a 64-year-old postmenopausal woman who was found to have an underarm mass for 3 months. Ultrasonography (US) and computed tomography (CT) suggested possible breast cancer with axillary lymph node metastasis. The patient underwent left modified radical mastectomy combined with axillary lymph node dissection. The postoperative pathology suggested a binary tumor, and we performed comprehensive treatment.We share the treatment of a rare case of triple-negative para-breast cancer complicated with carcinoma in situ of the breast, hoping to have new therapeutic ideas for the treatment of this disease.